Seed vigor and productivity - Filgueiras, Tarciso S. (Pesquisa Agropecuaria Brasileira, 2014)
Seedling vigor is deeply related to productivity to the extent that high vigor seeds are expected to form better stands and produce higher yields. Seed vigor is here broken clown in the following components: seed maturity, seed size, nature of food reserve, seed deterioration and seedborne pathogens. Each component is briefly dealt with and its implication in productivity discussed. It is recommended the use of high vigor seed lots and suggestion is made to the seed companies to use vigor as a competition weapon.